PENGEMBAGAN LEMBAR KERJA SISWA BERBASIS KONTEKSTUAL UNTUK MEMBENTUK LITERASI SAINS PADA PEMBELAJARAN FISIKA MATERI LISTRIK DINAMIS KELAS IX SMP - Elviza, Rully; ', Azizahwati; Ma‟ruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to produce student worksheet based on contextual to form science literacy that valid. Benefits of this research is the product can be used as teaching material teacher guide, increaseknowledge of science , guiding students in self-development as well as providing literacy skills of science and students' critical thinking skills. The research method used is Research and Development (R & D). Method steps include potentials and problems, literature and information review, product design, validation, and proven design. The result of the research shows the validity of LKS stucture is 100% with High category. In the validity of the contents of the LKS done twice with the results of the first validation of 76, 83% with high category but not valid because there are still indicators Low category. After making the improvement, the second validation result is 80.08% with High category. The Student Worksheet is declared valid and suitable for use by the school as a teaching material and is recommended to continue the research in the form of application as a trial to the school with the manufacture of mass products.Keywords: Student Worsksheet, Contextual Learning, Sciene Literacy